2006
DOI: 10.1364/ol.31.002927
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous visualization of spatial and chromatic aberrations by two-dimensional Fourier transform spectral interferometry

Abstract: We demonstrate the use of a simple tool to simultaneously visualize and characterize chromatic and spherical aberrations that are present in multiphoton microscopy. Using two-dimensional Fourier transform spectral interferometry, we measured these aberrations, deducing in a single shot spatiotemporal effects in high-numerical-aperture objectives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 14 publications
0
33
0
Order By: Relevance
“…In multiphoton microscopy, spatial aberrations are ultimately coupled to temporal distortions. The extent of this coupling can be precisely determined by using two-dimensional spectral interferometry (2DSI) [13]. Specifically, one can extract the impact of the spatial distortions on pulse duration.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In multiphoton microscopy, spatial aberrations are ultimately coupled to temporal distortions. The extent of this coupling can be precisely determined by using two-dimensional spectral interferometry (2DSI) [13]. Specifically, one can extract the impact of the spatial distortions on pulse duration.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…For example, 2DSI measurements on a 1.25 NA Zeiss objective indicated that for pulse durations greater than 50 fs, spherical aberration is dominant, and while the focus broadens spatially as a result of this distortion, the impact on pulse duration is negligible. Conversely, for pulse durations on the order of 15 fs, the chromatic aberration is dominant, and will result in broadening the pulse duration to approximately 25 fs [13]. In the case of these very short pulses, distortions are a complex mix of radially varying aberrations.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…One of the most common methods used for the measurement of spectral phase shift is the so-called spectrally resolved interferometry, SRI [63][64][65][66][67][68][69][70][71][72], which can be interpreted as a special case of SSRI when α = 0. The beams here leave the Michelson or Mach-Zehnder interferometer in a collinear manner, and an interference is established due to the temporal delay t* within the time scale of the coherence time, kept to be constant between the beams.…”
Section: Spectrally Resolved Interferometrymentioning
confidence: 99%
“…44 Finally, it should be noted that entirely linear, interferometric methods can be used to characterize the focus. 40,45,46 Jasapara et al used spectrally resolved interferometry to characterize how 10 fs pulses were distorted when focused by a 205 and a 1005 0.85 NA. objectives.…”
Section: B Characterization Of Pulses At the Focus Of A High Na Opticmentioning
confidence: 99%